Studies on Kutadgu Bilig During the Soviet Period (Eurasian Journal of Philology Science and Education, 2025)
During the era of the Soviet Union, Kazakh philological science, including historical lexicology, has undergone a significant stage of development. Starting with studies of ancient Turkic runic monuments and medieval written monuments, significant progress was made. In most cases, these studies were fundamental in nature. However, this process was carried out under strict ideological control. This is how the so-called political culture of scientific interpretations of the objects under study appeared. These statements in most cases had a collective character, in other words, they were presented as a concept of the socialist system. These tendencies also affected the study of medieval written monuments; Yusuf Balasaguni’s Kutadgu Bilig, a didactic poem in verse, was no exception. The article also notes the Kazakh interpretation of the title as “Knowledge that brings happiness” (“Құт әкелетін білім”) and refers to related scholarly publications, including a 1999 edition published in Istanbul and a 1996 Uyghur-language publication issued in Almaty. A collective edition in Kazakh in 1971 was published as a textbook for university students. Short extracts from these publications were given, as well as a short review of the academic edition of Kutadgu Bilig in Kazakh. In addition, Emir Nadjip’s book, published only in 2000, was also relevant to the study of medieval Turkic scripts. The article used thematic commentaries of academic editions published both in modern times and during the Soviet era.Keywords: Yusuf Has Hajib, Soviet Turkology, historical lexicology of the Kazakh language, Istanbul edition, Kashkaria, Turkic languages, Sovietism, translation.